STUDY ON THE NUMERICAL SIMULATION IN THE PROCESS OF ROLLING WAVE AND ECCENTRIC CIRCULAR WITH RADIATING CORRUGATED RIBBON - ZHAO XianFeng; SHI HongYan; CHEN XiaoYu; ZHOU ShunJun (Jixie qiangdu)
In order to analyze the change law of stress of aluminum chaff in the process of rolling waves,and the reasons of the eccentric circular to get the accurate wave of radiating corrugated ribbon,the model of bilinear isotropic harden was established to simulate the process of rolling wave in the Ansys Workbench.The result of rolling wave Aluminum chaff was verified on the machine of rolling wave.The results show that the curve of stress is the form of wave which correspond to the wave of aluminum chaff; The residual stress of aluminum chaff reduce along the arc of peak,while the reduce is asymmetric distribution on both sides,which is the reason of the eccentric circular; due to the meshing movement of tool,the plastic strain increased to the maximum in stages; the model of actual rolling waves match with the the theory modal,which verify the correctness of the analytical method.